2003
DOI: 10.1177/1069072703011002001
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge and Promise of Cognitive Career Assessment

Abstract: Abilities are as important as interests in career choice and development. Reviving cognitive assessment in career counseling promises to help counselees better understand their career options and how to enhance their competitiveness for the ones they prefer. Nearly a century of research on human cognitive abilities and jobs' aptitude demands in the U.S. economy reveals that the two domains are structured in essentially the same way. The author describes that common structure and how it can be used in assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 27 publications
3
115
0
4
Order By: Relevance
“…E. Snow et al, 1996;Tyler, 1974;Williamson, 1965). Although the latter clearly influence the educational-vocational niches that people self-select into (approach), the niches that people select out of (avoid) are influenced by the former (Gottfredson, 2003;Lubinski, 2004;Scarr, 1996;Scarr & McCartney, 1983). When overall profile similarity was evaluated, by sex, using math-science graduate students as a criterion reference, female adolescents with high spatial ability were more congruent with their same-sex graduate student counterparts than were female adolescents with relatively low levels of spatial ability, which solidify the above conclusions for females.…”
Section: Discussionmentioning
confidence: 99%
“…E. Snow et al, 1996;Tyler, 1974;Williamson, 1965). Although the latter clearly influence the educational-vocational niches that people self-select into (approach), the niches that people select out of (avoid) are influenced by the former (Gottfredson, 2003;Lubinski, 2004;Scarr, 1996;Scarr & McCartney, 1983). When overall profile similarity was evaluated, by sex, using math-science graduate students as a criterion reference, female adolescents with high spatial ability were more congruent with their same-sex graduate student counterparts than were female adolescents with relatively low levels of spatial ability, which solidify the above conclusions for females.…”
Section: Discussionmentioning
confidence: 99%
“…(pp. i-ii) Gottfredson (2003) reviewed literature on measures of ability as related to career success and concluded that (a) general ability factor, g, was the best predictor of career achievement, and (b) specific types of ability were not necessary to predict career success for most occupations. Therefore, we decided not to use the Mechanical Comprehension, Auto and Shop, or Electronics Information scales in our study because they assess specific knowledge rather than general ability.…”
Section: Sesmentioning
confidence: 98%
“…In addition, Strenze identified the importance of ability as a predictor of earnings later in life. Gottfredson (2003) reviewed a large number of studies of the relationship between cognitive ability and career accomplishments and concluded that general cognitive ability, g, was the strongest predictor of career success in many occupations. Another important implication of empirical studies on predictors of career success is the relationship between socioeconomic background and ability.…”
Section: Background Variables and Success In Midlifementioning
confidence: 98%
“…Advisors and counselors are sometimes reluctant to broach this matter with students (L. S. Gottfredson, 2003). However, Holland's theory provides some tools to help in this undertaking, and these can be useful in improving advising and counseling services.…”
Section: Holland-based Research On College Students and Facultymentioning
confidence: 99%